Gang violence predictability: Using risk terrain modeling to study gang homicides and gang assaults in East Los Angeles. (September 2018) - Valasik, Matthew
Abstract: Purpose: The current study investigates the application of risk terrain modeling (RTM) to forecast gang violence. RTM is routinely utilized to predict future criminal events in micro-units (i.e., city blocks) based upon features of the physical environment. The particular focus of the current study is RTM's ability to separately predict future gang assaults and gang homicides in the Los Angeles Police Department's (LAPD) Hollenbeck Community Policing Area. Method: Guided by the existing gang literature and knowledge of the region, 22 environmental risk factors are anticipated to spatially influence gang assaults and gang homicides. An RTM is established for 2009 gang assaults and 2009–2011 gang homicides. The RTM is then used to predict 2012 gang assaults and 2012 gang homicides respectively. Results: Places most at risk of experiencing a gang assault are in close proximity to where gang members are frequently observed loitering by police and Metro rail stops while also contending with residential concentrations of local gang members. Areas most at risk of experiencing a gang homicide cope with residential concentrations of local gang members and gang set space. The ability for RTM to successfully forecast future gang violence may be limited. Conclusions: RTM is able to successfully identify and evaluate meaningful environment risk factors that spatially influence gang assaults and gang violence. However, the ability for RTM to successfully forecast future gang violence may be limited. Highlights: Study investigates the application of risk terrain modeling (RTM) to forecast gang violence. Particular focus is on RTM's ability to seperately predict areas at risk of future gang assulats and gang homicides. Risky areas for gang assualts are near members' loitering spaces and rail stops in concert with clusters of members' homes. Areas most at risk of experiencing gang homicides cope with concentrations of gang member residences and gang set spaces. RTM identifies relevant risk factors that spatially impact gang homicides, yet, forecasting future events may be limited.